PEMODELAN SPASIAL BAHAYA BANJIR ROB BERDASARKAN SKENARIO PERUBAHAN IKLIM DAN DAMPAKNYA DI PESISIR PEKALONGAN - Marfai, Muh Aris (Bumi Lestari, 2013)
Abstract Tidal flood is predicted to be more severe in the future because of sea level rise due to global warming. Purposes of the study are: 1) identify spatial distribution of tidal flood hazard in Pekalongan coastal area; 2) identify environmental impacts of tidal flood in Pekalongan coastal area; and 3) formulate coastal management based on spatial distribution analysis and tidal flood impacts in Pekalongan. Flood analysis in coastal area was conducted by flood hazard mapping using GIS (Geographic Information System). Flood hazard mapping was developed by integrating GIS operation with DEM (Digital Elevation Model), level of inundation and iteration process. Tidal flood inundation scenario was generated based on highest tides and sea level rise scenario by IPCC 2007, level of inundation reached up to 135 mm. Results of this study showed that settlement and irrigated paddy fields are the widest inundated area by tidal flood. Tidal flood provides serious environmental impacts such as infrastructure damage, agriculture and aquaculture land damage, and soil and water pollution. Infrastructure damages include road, settlements and sanitation.
Keywords: Keywords: tidal flood, environmental impact, coastal management, spatial modelling, climate change scenario